Effect of Different Kinesio Taping Interventions on the Local Thresholds of Current Perception and Pressure Pain in Healthy Adults - Liu, Kun; Yin, Lulu; Ma, Zheng; Yu, Bo; Ma, Yanhong; Huang, Lihua (Frontiers in Physiology, 2020)
Objective Previous studies made controversial claims about the alleged effects of Kinesio Taping (KT) on pain relief. To date, the mechanism by which KT relieves pain remains unclear. Moreover, pain evaluation lacks objective and quantitative parameters. This study compared the acute effects of different KT interventions on the local thresholds of pressure pain and current perception in healthy adults to determine the potential mechanisms by which KT relieves pain. Methods Thirty healthy female subjects randomly received four KT interventions, namely, no taping (NT), placebo taping (PT), Y strips of KT (KY) and fan strips of KT (KF), on the waist. Current perception threshold (CPT), pressure pain threshold (PPT), soft tissue hardness and the visual analogue scale (VAS) scores of the subjects’ perceived pain were immediately measured after taping. Repeated-measures ANOVA was performed to determine significant differences in these parameters among the four interventions. Results Significant differences in CPT values among the interventions were observed at the frequency of 5 Hz (F = 3.499, p = 0.019, ηp2 = 0.111). Post-hoc analysis revealed that CPT was significantly higher for KF than for NT (p = 0.008, 95% CI = 1.390–11.990). Significant differences in PPT values (F = 4.352, p = 0.012, ηp2 = 0.130) and soft tissue hardness (F = 2.957, p = 0.049, ηp2 = 0.093) were observed among the different taping conditions. Post-hoc analysis revealed that PPT was significantly higher for KF than for PT (p = 0.011, 95% CI = 0.071–0.749) and soft tissue hardness was significantly higher for KF than for NT (p = 0.010, 95% CI = 0.461–4.586) and KY (p = 0.040, 95% CI = 0.059–3.800). No significant differences in self-perceived pain among the interventions were observed. Conclusion The healthy adult females had higher PPT values, lower soft tissue hardness and higher CPT values at 5 Hz under KF intervention applied on the waist than those under the other taping interventions. Moreover, the different taping conditions had no significant differences in terms of VAS of perceived pain. These results provide guidance for the application of KT on pain management.